The Effect of Neighborhood Selection on Collaborative Filtering and a Novel Hybrid Algorithm. Issue 2 (3rd April 2017) - Milli, Musa; Bulut, Hasan
Abstract: Recommender systems are widely used in industry and are still active research areas in academia. For many businesses, they have become indispensable business tools. Producing accurate results for such systems is important for the operations of the businesses. For this reason, various algorithms and approaches have been developed for recommender systems to increase the prediction accuracy. Collaborative filtering is one of the most successful approaches. In collaborative filtering, in order to predict more accurately, it is recommended to determine user's active neighbors. k -nearest neighbor ( k -NN) algorithm is one of the most widely used neighbor selection algorithms. However, k -NN algorithm uses a fixed k value that reduces the accuracy of the prediction. In this paper, we present two novel approaches to increase the prediction accuracy of recommender systems; k %-nearest neighbor ( k %-NN) algorithm to determine the appropriate k value for a user and a hybrid algorithm that combines a collaborative filtering technique and content-based approach. Our test results demonstrate that k %-NN algorithm increases the average prediction accuracy compared to the traditional k -NN algorithm. Additionally, when the proposed hybrid algorithm is used with k %-NN, it produces more accurate results than the conventional collaborative filtering technique and content-based approach.